New Man. - Merton, Thomas (Bloomsbury Publishing, 2003)
The New Man shows Thomas Merton at the height of his powers and has as its theme the question of spiritual identity. What must we do to recover possession of our true selves? By way of an answer, Merton discusses how we have become strangers to ourselves by our dependence on outward identity and success, while our real need is for a concern with the image of God in ourselves. At a time of retrieval of our religious traditions, Merton's voice is both intelligent and spiritually compelling. Thomas Merton, a Trappist monk, is perhaps the foremost spiritual thinker of the 20th century. His.